Screening and isolation of cold-adapted cellulose degrading bacterium: A candidate for straw degradation and De novo genome sequencing analysis - He, Zhigang; Ding, Baopeng; Ali, Qurban; Liu, Huiyu; Zhao, Ying; Wang, Xiujuan; Han, Yingzuo; Dong, Huan; Divvela, Praveen Kumar; Juan, Yinghua (Frontiers in Microbiology, 2023)
To solve the problem of difficult degradation of corn straws under low temperature. The study was conducted in low-temperature (10°C) and high-efficiency cellulose-degrading bacteria were screened using carboxymethyl cellulose (CMC) selection medium and subjected to genome sequencing by the third-generation Pacbio Sequl and the second-generation Illumina Novaseq platform, and their cellulase activity was detected by 3,5-dinitrosalicylic acid (DNS) method. The results showed that the low-temperature (10°C) and high-efficiency cellulose-degrading bacterium Comamonas sp. K1 was 4,060,823 bp in genome size, containing 4,213 genes, with 3,665, 3,656, 2,755, 3,240, 1,261, 3,336 and 4,003 genes annotated in the non-redundant protein sequence database (NR), Pfam, clusters of orthologous groups of proteins (COGs), Genome Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Annotation databases, respectively. In addition, a large number of lignocellulose degradation-related genes were annotated in the genome. The cellulose activity of Comamonas sp. K1 was higher, among which β-glucosidase (BG) had the highest activity, followed by endoglucanase and exoglycanases. It was found that through adding low-temperature straw decomposing bacteria in the corn straw composting experiment at 6°C, the average temperature of straw composting (58.7°C) was higher 86.7% increment, the humic acid/fulvic acid (HA/FA) ratio in humus was increased by 94.02%, and the degradation rate of cellulose and hemicellulose rose by 28.57% and 41.39%, compared with that of the control. The results provide a theoretical basis for clarifying the degradation mechanism of low-temperature cellulose-degrading bacteria and improving the cellulose degradation efficiency.